Grundlegende Untersuchungen zum Prozessverhalten von Silizium als Werkzeugwerkstoff für das Mikroscherschneiden metallischer Folien - Hildering, Sven (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2017)
The trend towards further miniaturisation of metallic components causes high demands on tools for mechanical manufacturing processes. Traditional tool production methods reach their technical and economical limits. Consequently, within this work an alternative approach is chosen by applying silicon etching for manufacturing micro punches with a width under 100 μm. Based on experimental and numerical investigations the fundamental process behaviour of silicon tools for micro blanking of thin metal foils is explaine